ANALISIS BAHAN BAKAR MINYAK HASIL PIROLISIS SAMPAH PLASTIK JENIS PP (POLYPROPYLENE )TERHADAP KARAKTERISTIK MINYAK YANG DIHASILKAN - Muhammad Hasby Ashsidiq; Dominggus G. H. Adoe; Defmit B.N. Riwu; Dantje A. T. Sina; Almido H, Ginting; Samy Y. Doo (Universitas Nusa Cendana, 2025)
This research aims to determine the density and viscosity of oil resulting from pyrolysis of plastic waste and to find out the relationship between density and viscosity of the pyrolysis oil produced. This research was carried out using polypropylene (PP) plastic, with the reactor used being a single reactor with the reactor temperature set at 200c and 250c. The results of the research show that the density is 0.751 – 0.773 kg/l, the viscosity is 0.574822548 – 0.841376288 cPs, where during the research carried out density and viscosity have an interrelated relationship. Changes in pyrolysis temperature can significantly affect the viscosity and density of pyrolysis oil, besides that, different research times and materials can influence the results of the pyrolysis process.